Efficacy of United Nations Collective Security System to Prevent another World War - Shaikh Shohag Hossain (Law and Society Students' Journal, 2023)
The condition of humanitarian crises and conflicts around the world is growing tremendously. Today we are dealing with a classic repetition of history to the close calls of world war. Though the UN collective security System tried to solve the contemporary issues, their efforts are deprived of proper effectiveness. If the contemporary crisis of the Russia-Ukraine and China-Taiwan conflict continues at this speed, it is not very late that the world will face a third world war. Therefore, to avoid a Third World War regarding this issue, the UN and world leaders should take immediate steps to solve this destructive crisis and increase the protection of this crisis. History very rarely teaches people lessons. The Second World War teaches us a destructive form of war. This paper uses the doctrinal methodology to discuss the efficacy of the UN Collective Security System in preventing the next world war. The author analyzed historical implications and different international law concepts to assess the efficacy. The author also tries to discover the strengths and loopholes of the current UN Collective Security System and Responsibility to Protect (R2P). The author identifies the bifurcation of the current world, which may lead to the next world war.